2017
DOI: 10.1136/jech-2017-209165
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption in a general antenatal population and child neurodevelopment at 2 years

Abstract: Early binge exposure, followed by lower-level PAE, demonstrated an increase in sensation-avoiding behaviour. There were, however, no significant associations between PAE and neurodevelopment following adjustment for important confounders and modifiers. Follow-up is paramount to investigate subtle or later onset problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…The New Mexico cohort also found PAE to be significantly related to increased infant negative affect ( β = 8.60, p = 0.008 using the IBQ [Bakhireva et al., ]). In the Australia cohort (Halliday et al., ), binge exposure in early pregnancy with no more than low‐to‐moderate continued exposure was associated with abnormal sensory avoidance on the ITSP (OR 1.88, 95% CI: 1.03 to 3.41). PAE throughout pregnancy was also strongly negatively correlated with elicited play (where infant play is initiated through modeling behaviors of an examiner) in 13‐month infants in South Africa ( r = −0.34, p < 0.001) and somewhat attenuated by adjustment for socio‐environmental confounders ( β = 0.022, p < 0.05 [Molteno et al., ]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The New Mexico cohort also found PAE to be significantly related to increased infant negative affect ( β = 8.60, p = 0.008 using the IBQ [Bakhireva et al., ]). In the Australia cohort (Halliday et al., ), binge exposure in early pregnancy with no more than low‐to‐moderate continued exposure was associated with abnormal sensory avoidance on the ITSP (OR 1.88, 95% CI: 1.03 to 3.41). PAE throughout pregnancy was also strongly negatively correlated with elicited play (where infant play is initiated through modeling behaviors of an examiner) in 13‐month infants in South Africa ( r = −0.34, p < 0.001) and somewhat attenuated by adjustment for socio‐environmental confounders ( β = 0.022, p < 0.05 [Molteno et al., ]).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, PAE was associated with poorer BSID Mental/Cognitive scores in the Detroit ( r = −0.22 at 13 months, p < 0.05 for a 1‐sided test [Kaplan‐Estrin et al., ]), Ottawa ( r = −0.19 at 13 months, p < 0.05 [Gusella and Fried, ]), and Ukraine ( β = −2.91 at 6 months, β = −2.67 at 12 months, p 's < 0.05 [Bandoli et al., ]) cohorts. No significant differences on the BSID Mental/Cognitive scores in relation to PAE were found in the Australia ( β = 3.06, 95% confidence interval (CI): −1.19 to 7.30 at 24 months [Halliday et al., ]), New Mexico (mean cognitive scores in the moderate/mild PAE group: 102.4 ± 7.5 vs. No PAE: 101.3 ± 9.3 at 6 months, p > 0.05 [Bakhireva et al., ]), and Scotland (PAE 50 to 99 g AA/wk: β = 1.57; PAE ≥ 100 g AA/wk: β = −2.00; all analyses at 18 months, p 's > 0.05 [Forrest et al., ]) cohorts. Interestingly, in the Seattle cohort, BSID Mental/Cognitive scores were poorer in children with PAE at age 8 months (Streissguth et al., ), but normalized when reassessed at 18 months (Streissguth et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the validity of data on prevalence, as well as the conclusions on the effects on early child development, should be improved. In comparison with the negative effects based on high amounts of consumption, the influence of low and moderate amounts of alcohol and nicotine exposure is scarcely understood 16,17 . The number of studies remains small, with inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with the negative effects based on high amounts of consumption, the influence of low and moderate amounts of alcohol and nicotine exposure is scarcely understood. 16,17 The number of studies remains small, with inconsistent results. Previous review papers reported results that focussed on different developmental outcomes.…”
mentioning
confidence: 99%